Haplostominae (Copepoda, Cyclopoida) associated with compound ascidians from the San Juan Archipelago and vicinity - Ooishi, Shigeko; Illg, Paul L. (Osaka, Japan Nippon Publ., 1977)
Special Publication from the Seto Marine Biological Laboratory; Series V December, 1977
Keywords: Haplostominae--Classification--San Juan archipelago; Cyclopoida--San Juan archipelago